Pirólise térmica e catalítica de resíduos de vácuo gerados no refino de petróleo - Lima, Regineide de Oliveira (2012)
In this study, was used a very promising technique called of pyrolysis, which can be used for obtaining products with higher added value. From oils and residues, since the contribution of heavier oils and residues has intensified to the world refining industry, due to the growing demand for fuel, for example, liquid hydrocarbons in the range of gasoline and diesel. The catalytic pyrolysis of vacuum residues was performed with the use of a mesoporous material belonging the M41S family, which was discovered in the early 90s by researchers Mobil Oil Corporation, allowing new perspectives in the field of catalysis. One of the most important members of this family is the MCM-41, which has a hexagonal arrangement of mesopores with pore diameters between 2 and 10 nm and a high specific surface area, making it very promising for use as a catalyst in petroleum refining for catalytic cracking, and their mesopores facilitate the access of large hydrocarbon molecules. The addition of aluminum in the structure of MCM-41 increases the acidity of the material, making it more positive for application in the petrochemical industry. The mesoporous material of the type Al-MCM41 (ratio Si / Al = 50) was synthesized by hydrothermal method starting from the silica gel, NaOH and distilled water added to the gel pseudobohemita synthesis. Driver was used as structural CTMABr. Removal of organic driver (CTMABr) was observed by TG / DTG and FTIR, but this material was characterized by XRD, which was observed the formation of the main peaks characteristic of mesoporous materials. The analysis of adsorption / desorption of nitrogen this material textural parameters were determined. The vacuum residues (VR's) that are products of the bottom of the vacuum distillation tower used in this study are different from oil fields (regions of Ceará and Rio de Janeiro). Previously characterized by various techniques such as FTIR, viscosity, density, SARA, elemental analysis and thermogravimetry, which was performed by thermal and catalytic degradation of vacuum residues. The effect of AlMCM-41 was satisfactory, since promoted a decrease in certain ranges of temperature required in the process of conversion of hydrocarbons, but also promoted a decrease in energy required in the process. Thus enabling lower costs related to energy expenditure from degradation during processing of the waste